BIG DATA ANALYSIS IN EDUCATION - Muratov Elvin Ilyich (Scholar Express Journals, 2023)
Today, information is the basis of any modern educational process, a tool for effective management and optimization of learning processes. Big data analytics will help to identify and even prevent many problems in training in a timely manner. To understand the possibilities of modern technologies and choose among them the best ratio of quality and result, the teacher needs to understand the basic concepts (Big Data). Today, in our Republic, much attention is paid to the education and training of modern personnel in all areas (Big Data) is one of the good tools for solving these problems.
Keywords: Digital age; machine learning; Big Data